Extreme Wind Fragility Assessment for Window System Failure in Lightweight Steel Frame Structure in Korea - Viriyavudh Sim; Yongju Gwak; Woo Young Jung (Journal of ICT, Design, Engineering and Technological Science, 2017)
In this research, we concentrate on defining the initial step in the framework of probability risk assessment of wind loads by developing wind fragility on small-scale residential facilities in South Korea, i.e., the window system installed in a lightweight steel frame house. The study was to develop a fragility model using random variables according to the wind loads parameters and the resistance capacity of the window system. Design- and material-based experimental results in typical residential facilities in South Korea provided capacity parameters, i.e., resistance capacity of the window system, which allow us to obtain the failure probability of the window system under various limit conditions and consequently be used to evaluate the vulnerability of windows in this small residential steel house. The study has successfully proved that the most vulnerable are the leeward windows, i.e., opposite to the wind direction. Usage of this methodology could lead to a more predictable structure performance and facilitate the introduction of performance-based design guidelines for this component of building. Fragilities such as those presented here also can be convolved with wind hazard curves to develop a risk assessment tool, which can evaluate the potential impact of a natural hazard in public planning and mitigate the consequent economic losses and social disruption.